Efesiensi dan Efektifitas dalam Menajemen Keuangan Lembaga Pendidikan - Aburizal Anshori; Fathona Khoirunnisah; Restiyeni Aulia; Hesti Kusumaningrum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to explore the concepts, objectives, functions, and principles of financial management in educational institutions. With the increasing complexity of educational institutions, efficient and effective financial management has become a crucial factor in supporting the creation of quality education. To achieve this goal, the study uses a literature review method. Data sources were obtained from various academic journals, reference books, and publications related to financial management in educational institutions. The results of the study show that good financial management plays an important role in supporting the overall management of education. This is achieved through the optimization of available financial resources, management of facilities and infrastructure, and improvement of the welfare of educators. The implementation of effective financial management enables educational institutions to allocate funds more strategically, thus supporting various educational programs and activities. With good financial management, it is expected that the quality of education provided by educational institutions can continue to improve over time.